Analysis and Development of Project Monitoring Information Systems Using RESTful API Echo Framework at SMK Negeri 2 Klaten - Rachelita Embun Safira; Handaru Jati (Journal of Information Technology and Education (JITED), 2023)
Based on the results of observations, project monitoring activities at SMK N 2 Klaten still use manual methods, so it is less effective to implement. This research aims to (1) streamline the monitoring, guiding, and storing of progress documentation in the SIJA department of SMK N 2 Klaten through designing and developing a project monitoring information system, (2) meet quality standards ISO/IEC 25010. The research was conducted using the Research and Development (R&D) method, developed using the SDLC (System Development Life Cycle) method with the Waterfall model, which consists of the stages of needs analysis, design planning, coding, testing, and management. Quality analysis is done using the ISO/IEC 25010 standard on several aspects, namely (1) functional suitability, (2) usability, (3) performance efficiency, (4) reliability, and (5) portability. The results obtained include: (1) A website-based project monitoring information system developed using the waterfall development model, using the Gorm, Echo, and Vue.js frameworks. (2) The results of testing the quality of the ISO/IEC 25010 system are the functional suitability aspect with a score of 1 (very good), the aspect of use with a proportion of 80% (feasible) with an Alpha Cronbach score of 0.957 (very good), the efficiency of the performance aspects with a score of 99.81% (very good) for performance and 98.9% (very good) for structure, aspect of reliability with a score of 100% (has met), as well as the aspect of portability has been fulfilled because it can be run on various browsers, both desktop and mobile.